Prioritization of Medicinal Plants for Cultivation in Karnataka-an Assessment through Participatory Approach - Ramesha, M. N.; Kempegowda, M. L.; Satyamadhava, L. V. (Indian Forester, 2011)
Study aims at selecting few medicinal plants, which have got good market prospects and suffered difficulties in propagation as well as ecological threats. With consent of all stakeholders’ twenty prosperous plant species were selected as mandatory crops for proposed medicinal plants seed centre in Karnataka. Concept development meeting (CDM), Cyber link to stakeholder, field survey and consultative meeting worked well to approach stakeholders across the state. The seed centre would be set up by Karnataka Forest Department for promotion of medicinal plants cultivationin the state.